Probability Model for Intrusion Detection System in Mobile Adhoc Network - P, Bharathisindhu; S.SelvaBrunda, Dr (International Journal of Engineering and Technology, 2018)
Wireless technologies increasingly exist everywhere in advanced networks; however, this new innovation accompanies its own set of challenges. The nodes in the wireless network are characteristically ‘open’ and viewable by all network scanners. Networks are protected using many firewalls and encryption software’s. Firewalls restrict access between networks to prevent intrusion and do not indicate an attack within the network. An Intrusion Detection System (IDS) is required which monitors the network, detects misbehavior or anomalies and notifies other nodes in the network to avoid or punish the misbehaving nodes. In this paper, we propose a probability based IDS model that provides generalized solution to detect set of malicious nodes to improve the detection speed and accuracy.
Keywords: Attacks; Intrusion Detection; MANET.